Innovation Of Bay Tat Cake In The Perception Of Generation Z In Napal Bengkulu Village - Balqis, Aisyah Shinta; Astuti, Nugrahani; Lukitasari, Febriani; Lebdoyono, Rendra (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The preservation of Bengkulu's traditional Bay Tat cake faces the challenge of attracting attention among Generation Z. Currently, Bay Tat only has two variants (pineapple and coconut kernel), even though the potential of Bengkulu's local food ingredients is very diverse, allowing for the development of new flavor variants. However, the perception of Generation Z as future consumers towards the potential of Bay Tat innovation is unknown, including whether Generation Z will be interested if Bay Tat cake is innovated. This study aims to describe the perception of Generation Z in Napal Village towards the potential of Bay Tat cake innovation based on four questionnaire indicators: motives, willingness and expectations, stimulus intensity, and stimulus repetition. The method used is descriptive quantitative with 81 Gen Z respondents (junior high school students, high school students, university students, and workers) who are familiar with or have consumed Bay Tat. Data were collected through a closed questionnaire with a Likert scale of 1–5 and analyzed descriptively using Microsoft Excel. The results show that Generation Z's perception of the potential of Bay Tat innovation is in the positive category, marked by the dominance of "Agree" and "Strongly Agree" answers in all indicators. The 85% approval rate indicates that the younger generation is open to the development of new Bay Tat flavors, thus offering the opportunity for innovation in this traditional product to remain relevant to young consumers. The implication of this finding for the world of education is that it can be used as a real-life example in Product Development or Culinary Entrepreneurship courses to help students understand how to develop traditional foods to make them more appealing to the younger generation.